Changes in the ecological system of coastal areas of Bantul and Kulon Progo Regencies - Wahyudi, Muhammad; Poedjirahajoe, Erny; Hermawan, Much. Taufik Tri; Djumanto, Djumanto (Indonesian Journal of Geography, 2025)
Coastal areas are classified as highly vulnerable because they are always tied to changes in the global aquatic environment. The ecosystem dynamics are increasingly complicated and complex as a result of interactions with other systems on land. This phenomenon is very visible in the coastal areas of Bantul Regency and Kulon Progo Regency. We use Sentinel-2 satellite image interpretation in the period 2013-2022 as a historical record of land use change, and then explore it with Niklas Luhmann's social system theory to understand how communities and government mean the ecological system represented by activities in coastal areas. The results showed that the community and the Government massively changed the original ecosystem of pes-caprae with the dominant afforestation of shrimp cypress. For the community, afforestation is assumed to support production agriculture, from subsistence agriculture. For the government, afforestation is a misconception about reforestation and protecting vital infrastructure such as Yogyakarta International Airport. The main capital for change is technology and its knowledge, and economic capital obtained from production. The economic capital obtained is used for social transformation, including eliminating the stigma of poor, uninformed, and inferior coastal communities. The results achieved change the meaning of land from previously only to support daily livelihoods to production factors that have very high economic and social value. Any attempt to change the establishment of the social and economic system will be met with strong resistance from the community. Under these conditions, the sustainability discourse that we are developing is to build an institutionalized knowledge system, which is carried out repeatedly and continuously, which is important for the community to understand because its dynamics will continue to develop in the future.Received: 2024-10-23 Revised: 2025-02-07 Accepted: 22025-04-16 Published: 2025-04-30